The Black woman's guide to overcoming domestic violence: tools to move beyond trauma, reclaim freedom, and create the life you deserve - Moore-Lobban, Shavonne J. (New Harbinger Publications, 2022)
Understanding domestic violence -- Intersecting identities: unique struggles -- Faced by Black women -- Why survivors stay and how survivors can leave -- Building safety -- Learning to trust yourself and others -- Cultivating self-esteem and self-worth -- Letting go of guilt and shame -- Recognizing your power and reclaiming control -- Choosing intimacy -- Next steps: self-care and seeking support for survivors -- For friends, family, non-abusive intimate partners, clergy, and mental health care professionals.